Prospective randomised trial comparing traditional suture technique with the dynamic sliding loop suture technique in the closure of skin lacerations. Issue 1 (1st January 2003) - Gandham, S G; Menon, D
Abstract : Objective: The aim of this study was to compare the cosmetic appearance and related complications of selected skin lacerations closed by traditional suture technique with that of the dynamic sliding loop suture technique. Design: Prospective, randomised clinical trial. Setting: A district general hospital. Participants: Thirty seven eligible patients aged between 16 and 60 years with skin lacerations (no deeper than superficial fascia) to the limbs, trunk, and neck (excluding face and scalp) and with no associated neurovascular or tendon injuries were recruited into the trial. The exclusion criteria used included immunocompromised patients (diabetics, malignancy, renal failure, corticosteroid treatment), primary dermatological conditions (psoriasis, eczema), keloid prone or susceptible patients, and wounds judged unsuitable for primary closure. Intervention: Skin lacerations were randomly allocated to have closure by either the traditional method or by use of the dynamic sliding loop suture method. The trial had ethical approval of the hospital ethics committee and all participants were fully informed of the trial both verbally and by an information leaflet. Written informed consent was obtained before starting the study. Main outcome measure: The cosmetic appearance of photographs of wounds immediately after suture removal and at three months were assessed by a general surgeon and an orthopaedic surgeon blinded to the technique used. The 10 point visual analogue cosmesis scale was used for scoring the appearance of the wounds. Secondary outcome measure: The presence of wound closure related complications such as infection, dehiscence, suture slippage, wound edge submergence, skin edge necrosis, and haematoma formation were noted and recorded on follow up visits. Results: A total of 37 patients participated in the trial over a period of 18 months. Seventeen patients underwent suture by the traditional technique and 20 by the dynamic sliding loop suture technique. Four patients (all from the traditional group) were lost to follow up and not included in the study. Most wounds healed uneventfully although there was one case of wound infection in each group. Four patients had ligature slippage (three from the dynamic suture and one from the traditional group). Two patients had evidence of skin edge necrosis both from the traditional technique group. A comparison of the healed wounds by two independent assessors blinded to the technique used showed no statistically significant difference observed between the two types of intervention (Wilcoxon matched paired test p>0.05) immediately after suture removal or at three months. Although there was no statistically demonstrable difference, the comparative paired absolute visual analogue scores seemed to consistently show higher values for the sliding loop technique. Conclusion: The cosmetic appearance of wounds sutured using the dynamic sliding loop suture technique in this study were not statistically shown to be superior to those sutured using the traditional suture technique although absolute visual analogue scores consistently showed higher values for the sliding loop technique. The significance of this is unclear and may warrant a much larger trial to see if it is a trend that a larger population of participants can help to support or refute with regard to the superiority of this new technique.